The Use of Routine Blood Cultures in Pediatric Appendicitis. Issue 12 (December 2017) - Thompson, Graham Cameron; Morrison, Ellen; Ross, Marshall; Liu, Helena; Vanderkooi, Otto G.; Eccles, Robin
Abstract : Objectives: To determine the proportion of true-positive blood culture results in children presenting to the ED with suspected appendicitis. To describe the current practice of obtaining blood cultures in children with suspected appendicitis. Methods: We performed a 2-year retrospective health record review of all children aged 2 through 17 years investigated for suspected appendicitis at a tertiary Pediatric Emergency Department. Subjects were identified by searching (a) institutional records for ICD-10-CA coding, (b) diagnostic imaging records of ultrasounds for appendicitis, and (c) surgical database records for nonincidental appendectomies. Abstracted demographic and clinical data were matched to regional laboratory services data to describe the performance and result of blood cultures. Results: Overall, 1315 children investigated for appendicitis were reviewed. Seven hundred fifty (57.0%) were girls, the average age was 11.7 years (SD, 4.0). Blood cultures were obtained in 288 (21.9%) of 1315 patients. Of the 11 (3.8%) cultures that were positive, only 1 (0.35%) was a true positive. Young age, high triage acuity, and presence of fever were associated with the acquisition of cultures ( P < 0.001 for all). The proportion of children undergoing appendectomy and the negative appendectomy rate was similar between those with and without blood culture ( P = 0.10 and P = 0.96, respectively). Conclusions: True-positive blood cultures are very rare in children presenting to the ED with suspected appendicitis. Given the potential for false-positive cultures and the social/economic implications of initial testing/retesting of false positives, the use of routine blood cultures for children with suspected appendicitis is not supported.